Reconstructing shaft orbit using angle measurement to detect bearing faults. (May 2020) - Bruand, Guillaume; Chatelain, Florent; Granjon, Pierre; Martin, Nadine; Duret, Christophe
Highlights: Shaft orbit contains useful information about the bearing health state. Orbits can be reconstructed using several angle measurement sensors. A mechanical model explains the underlying process. Bearing fault severity is estimated by analyzing the shaft displacements. Abstract: The use of Instantaneous Angular Speed (IAS) in condition monitoring of rotating machines is an appealing alternative to traditional approaches such as those based on accelerometers: the direct angular sampling characteristic of IAS measurements has proven to be a favoured framework to study mechanical phenomena involved in rotating machines. Physical models have been established to link the variations of IAS to torque disturbances in case of mechanical fault such as bearing failure. In this paper an original point of view is given on the IAS measurement by linking IAS variations and shaft vibrations. First the orbit of a rotating shaft is studied to show that it contains useful information about the health state of the bearing. Then angle position sensors traditionally used in IAS measurements are combined to reconstruct this orbit. It is shown that IAS measurements are sensitive to the shaft vibrations, which may be used advantageously to enhance the diagnosis possibilities. Finally the links between various defect sizes and the reconstructed orbits are investigated to propose a fault severity indicator.